Factors Influencing Individual Taxpayer Compliance with Tax Sanctions as a Moderating Variable at KPP Pratama Serpong - Muhammad Zidane Alfarizi; Muhammad Su’un; Muhammad Nur (Universitas Muhammadiyah Makassar, 2025)
This study investigates the factors influencing individual taxpayer compliance by examining the moderating role of tax sanctions at KPP Pratama Serpong. Taxpayer compliance plays a vital role in the success of self-assessment tax systems, where individuals are expected to fulfill their obligations voluntarily. This research focuses on the effects of taxpayer awareness and tax knowledge on compliance behavior, and explores whether tax sanctions can strengthen these relationships. Using a quantitative approach, data were collected from 100 individual taxpayers registered at KPP Pratama Serpong through structured questionnaires. The analysis was conducted using Partial Least Squares (PLS) to examine direct and moderating effects. The results indicate that taxpayer awareness and tax knowledge both have a positive and significant impact on compliance. Furthermore, tax sanctions strengthen the positive relationship between taxpayer awareness and compliance, but do not significantly moderate the relationship between tax knowledge and compliance. These findings imply that while awareness can be amplified by sanctions to improve compliance, knowledge alone may not be sufficient unless supported by other enforcement or educational measures. This study contributes to tax compliance literature by integrating behavioral and regulatory perspectives in an Indonesian context, and offers practical insights for policymakers aiming to improve tax compliance through strategic use of sanctions and taxpayer education. The research suggests that improving public understanding of tax obligations and enhancing perceptions of enforcement may lead to more sustainable compliance behavior, particularly during periods of economic uncertainty.